ERGONOMICAL EVALUATION ANALYSIS OF PEDAL OPERATED COCONUT DEHUSKER. (International Journal of Food and Nutritional Sciences, 2022)
Agricultural operation's design takes into account human factors, traditional uses of coconuts, from food to cosmetics, attest to their well-known tremendous adaptability. Farm mechanization promotes the efficient use of machines to increase labour and land production. Additionally, it aids in cutting down on the laboriousness, expense, and duration of farming activities. In the tropics, the coconut palm is commonly grown. After the Philippines and Indonesia, India is the third-largest producer of coconuts worldwide. Thailand, Malaysia, Papua New Guinea, and the Pacific Islands are additional producers. India produces over 5500 million coconuts every year, with plantations covering more than a million hectares. About 0.35 million tones of copra are produced in the nation and India is responsible for 50% of global coir trade.